The Influence of the Working Climate and Motivation on the Performance of Employees in the Marine and Fisheries Service Boalemo County - Ratna Muhdin; Anis Naki; Ikram Muhammad (Journal of Economic, Business, and Administration (JEBA), 2021)
The objectives of this study are: 1) to find out how much influence partially the working climate has on the performance of employees in the Boalemo District Marine and Fisheries Service; 2) to find out how much influence partially motivates the performance of employees in the Boalemo District Marine and Fisheries Service; 3) to know how much influence simultaneously the working climate and motivation on the performance of employees in the Boalemo District Marine and Fisheries Service. The quantitative descriptive research method approach with the type of survey research that explains the causal relationship and performs hypothesis testing using a multiple regression analysis approach. The results showed that:1) the working climate has a positive and significant effect on the performance of employees in the Boalemo District Marine and Fisheries Service with an influence contribution of 55%. This means that the higher the working climate, the higher the performance of employees in the Boalemo District Marine and Fisheries Service; 2) motivation negatively and significantly affects the performance of employees in the Boalemo District Marine and Fisheries Service with an influence contribution of 72%. This means that the higher the motivation, the lower the performance of employees in the Boalemo District Marine and Fisheries Service; 3) simultaneously the influence of the working climate and motivation will have a positive and significant effect on the performance of employees in the Marine and Fisheries Service with a 59% contribution. This means that if the working climate and motivation are applied simultaneously it will further improve the performance of its employees.